Ottawa Ankle Rules in primary care - awareness, importance and use by family physicians - UZUNER, ARZU (TERMEDIA PUBLISHING HOUSE LTD, 2019)
Background. With the implementation by family physicians of the Ottawa Ankle Rules (OAR), which are clinical decision rules for ankle trauma, referral rates to secondary hospitals could be decreased and the majority of these problems could be resolved for patients in primary care. Objectives. The aim of this study was to determine the awareness levels of OAR among primary care physicians, and to show the importance of OAR. Material and methods. This research was planned as a volunteer-based, descriptive survey study conducted with practicing family physicians. An online questionnaire was delivered to participants through e-mail groups of family medicine associations over 3 months. Results. A total of 456 physicians responded to the questionnaire, comprising 307 (67.3%) females, and 149 (32.7%) males. OAR were known and used by 10.7% of the respondents. Most physicians thought OAR is appropriate for evidence-based medicine (94.5%), useful to clarify X-ray requirements (95%) and to reduce the cost of healthcare (94.3%). Conclusions. As the healthcare system requires primary care physicians to deal with traumatic ankle/foot injuries, there should be a greater awareness of the OAR, with information and training given to all primary care physicians.
Keywords: primary health care; algorithms; ankle fractures; CLINICAL-PREDICTION RULES; DECISION RULES; INJURIES; RADIOGRAPHY; IMPLEMENTATION; FRACTURES; EMERGENCY; FOOT